The Current Situation of Chinese Teaching in Higher Vocational Colleges - Liu, Tianxing; Liu, Shuang; Xu, Wenxiu; Li, Jingjing (Journal of Theory and Practice of Social Science, 2023)
The construction mechanism of high-quality student source base in Colleges and high schools is not perfect In order to keep up with the construction requirements of relevant education departments, some colleges and universities have some coping behaviors in the construction of high-quality student source base, and there is no perfect mechanism in the construction of high- quality student source base. For example, some colleges and universities have not carried out active promotion and implementation of supporting facilities after the establishment of high-quality student source base, as well as contact and interaction with students in this field, which leads to the active state of colleges and universities, while the high school is in a passive state. Over time, the driving force of cooperation between the two gradually declines, which is also an important factor affecting the cooperation between the two One. Therefore, in view of this phenomenon, colleges and high schools need to establish a scientific and reasonable evaluation system, and regularly evaluate the cooperation content and effect.